PENGELOLAAN PERUSAHAAN PERSERO BADAN USAHA MILIK NEGARA OLEH NEGARA UNTUK MEMAJUKAN KESEJAHTERAAN RAKYAT - Kurnia Saleh (SOL JUSTICIA, 2021)
This journal is entitled "The Role of the State in Managing State Owned Enterprises to Advance People's Welfare". The background of this thesis was the number of state-owned companies that were not optimal and causing losses to the state, even though the role of the state was very comprehensive in managing state-owned enterprises. On the other hand, the optimality of state-owned enterprises' function boiled down to the welfare of the people, so that the lack of optimality of state-owned enterprises also affected the people's welfare. There are several problems that arose from this condition which must be analyzed, namely: (1) what is the role of the state in the management of state-owned enterprises (2) how is the positive legal regulation of the role of the state in managing state-owned enterprises (3) what is the legal concept that should be carried out by the state in managing Limited Liability Companies to advance people's welfare. The method used in this research was normative juridical. The results of the research showed that the state played a major role in terms of regulation, governance management, and capital financing to state-owned enterprises. Legal arrangements and regulating dynamics on state-owned enterprises had started since the era of independence, the old order, the new order, towards reformation until post-reformation. The future legal concept that can be carried out by the state is by regulating the separation of BUMN assets strictly, encouraging the implementation of the principles of good corporate governance in the governance of state-owned companies, and affirming the position of BUMN not to be entered and intervened by politics